Illustrated capsules from the Advanced Course in Platelet Research - Christian Andrea Di Buduo; Vittorio Abbonante; Alessandro Malara; Alessandra Balduini; Amie K. Waller; Steve P. Watson; Eleyna M. Martin; Lloyd Bridge; Jonathan Gibbins; Ingeborg Hers; Claire Masson; Anita Eckly; et al. (Research and Practice in Thrombosis and Haemostasis)
This series of illustrated capsules summarizes the presentations made by the speakers at the first International Advanced Course in Platelet Research held in Murcia (Spain) from 27 to 28 September, 2024. This is the first course to receive a Fundamental Research Workshop Grant from the International Society on Thrombosis and Haemostasis (ISTH) and was also supported administratively and scientifically by the Spanish Society of Thrombosis and Haemostasis (SETH). This unique course focused on new methodologies applied in platelet research and how these are increasing our understanding of platelet formation, their multifunctionality in different physiological and pathological contexts, and contributing to the development of new platelet-targeted therapies to improve the management of hemostatic/thrombotic pathologies. It aligns with the objectives of several Scientific and Standardization Committees of the ISTH, including Platelet Physiology and Genomics in Thrombosis and Haemostasis, as well as with the academic objectives of the ISTH and SETH. The program was designed by the coordinator (J. Rivera), and the scientific advisory board (SAB: S.P. Watson, K. Freson, A. Balduini, and J. Di Paola) and comprised 9 scientific sessions with 25 presentations, each with time for extensive open discussion. Additionally, 33 abstract posters were presented, with the 3 highest scoring selected as oral presentations. The course was held in a single location and with an informal atmosphere to facilitate networking among participants. The course received very positive feedback from the 140 attendees. The course was supported by the ISTH, SETH, University of Murcia, CIBERER-ISCIII, Fundación Séneca (22426/OC/24), the United Kingdom Platelet Society and various pharmaceutical companies. We believe that the extraordinary scientific and human experience of this course may act as a stimulus for future courses.